A multiple case study on the use of stand-up desks in selected offices in Metro Manila - Tutanes, Melzon Louisse D. (College of Home Economics, University of the Philippines Diliman, 2019)
This research which utilized a multiple case study approach, sought to determine whether the use of stand-up desks had an impact on the employees' anthropometric concerns in selected offices in Metro Manila. Furthermore, the feasibility and acceptability of stand-up desks in the selected offices in Metro Manila was also examined. Using purposive sampling, four employees from Chevron Malampaya and another four employees from Pilipinas Shell were chosen as the respondents. Data gathering included interviews with a supplier of stand-up desks, interviews with the respondents and photo documentation of their work space. Anthropometrics and ergonomics were chosen as the theoretical framework that the study used. The respondents were assessed by their work routine with regards to their use of the stand-up desk. Their opinions about their health, work attitude, and productivity were also looked into. The results showed that all respondents found the use of the stand-up desk to be positive and cited that the stand-up desk improved their awareness of their health, most especially the strains in their muscles and bones. However, this study also suggests that the office culture and type of work affects the feasibility of the use of stand-up desks. Therefore, the study recommends the consideration of systems such as the Micropause and the Repetitive Strain Injury Protocol (RSIP) to improve the acceptability and impact of the stand-up desks. In addition to that, the study suggests that privacy is a factor of comfortability that may enhance the employees' work routine. Finally, the study recommends future researchers to consider assessing each employee's lifestyle and emotional or mental health as a way to investigate their work routine and office morale.